Engineering demand parameters for the definition of the collapse limit state for code-conforming reinforced concrete buildings. (1st September 2022) - Terrenzi, M.; Spacone, E.; Camata, G.
Abstract: This article discusses the main Engineering Demand Parameters (EDPs) found in the literature to define collapse of newly constructed reinforced concrete buildings. Currently, the definition of building collapse is still under debate, as different building codes and authors define them with different EDPs and even different values of the same EDPs.The EDPs can be defined locally (chord rotation, Local Damage Index, etc.) or globally (Inter-Story Drift Ratio, Roof Drift Ratio, Global Damage Index, etc.). A modified Global Damage Index that considers damage in both structural and non-structural elements is proposed in this paper The study compares the outcomes of some of these EDPs when applied to two case study moment-resisting reinforced concrete frames designed and analyzed in the framework of the RINTC — Reluis Project funded by the Italian Civil Protection Department (Ricci et al., 2018). One is a 6-story buildings (in Naples) the other a 9-story building (in L'Aquila). Nonlinear static and multiple-stripe dynamic analyses were carried out on 3D models with concentrated hinges. In addition to the above mentioned EDPs this study proposes and tests a new economic EDP that assumes that collapse is reached when the repair costs become larger than the reconstruction costs. Complete validation of the proposed economic EDP requires additional testing on code-conforming and, most importantly, on non-conforming older buildings, where brittle failures become an important issue. Highlights: Existing definitions of collapse for code-conforming buildings are compared. A suite of engineering demand parameters associated to collapse are investigated. A novel economic criteria associated to the buildings' collapse is proposed.